THE WORK OF ART + DOCUMENTATION AS MATERIAL + ART AS EVENT - Meers, Emily (Journal of Childhood Studies, 2025)
With children aged 2–5, we explored concepts around the ephemeral, temporal, and intangible aspects of artistic encounters and what these things do to us during an inquiry project. We entered into this with curiosity about the ways in which the unplanned and unknown aspects of an artistic encounter might push inquiry forward in unexpected ways that always require some sort of response. Situated the research within a posthumanist perspective, we explored some of the ways art as an event makes possible the ways that art and curriculum can and should be considered co-constructors of inquiry and sense making. A significant part of the project worked to disrupt conventions around documentation or pedagogical narration and to push the researcher (as well as the children and educators) to think of how we might incorporate documentation as a living, moving, active part of the process during artistic encounters and/or inquiry.